Association and Polymorphism of the APOA5 Gene Related to Carcass Characteristics and Lamb Quality in Sheep - Novita Nur Anggraeni; Kasita Listyarini; Ratna Sholatia Harahap; Cece Sumantri; Asep Gunawan (Buletin Peternakan, 2023)
The apolipoprotein A-V (APOA5) gene is a candidate gene that plays an important role in carcass characteristics and lamb quality. This study aimed to association and polymorphism of the APOA5 gene with carcass characteristics and lamb quality in sheep. The breed of sheep were used 100 sheep consisting of Thin Tailed Sheep (TTS) (n=55), Compass Agrinac Sheep (CAS) (n=10), Garut Sheep (GS) (n=18), Garut Composite Sheep (GCS) (n=8), and Barbados cross sheep (BCS) (n=9). Identification of APOA5 gene polymorphism was performed using PCR-RFLP method and association study was performed using GLM analysis. The results showed that the APOA5 (g.26929941 C>T) gene polymorphism was polymorphic in TTS, CAS, GS, and GCS, while BCS was monomorphic. The APOA5 gene has three genotypes (CC, CT, and TT). Association showed that the APOA5 was a significantly (P<0.05) associated with carcass percentage and carcass length. The polymorphism of the APOA5 (g.26929941 C>T) was also significant (P<0.05) associated with lamb quality of the pH dan tenderness. The TT genotype showed greater carcass length and pH than the CC and CT genotypes. The CT genotype showed a greater percentage of carcass and tenderness than the CC and TT genotypes. The APOA5 gene helps improve sheep carcass characteristics and lamb quality.